bahasa inggris - Syifa Maulia al Khairani; Dita Rizki Anggraini (Tarling : Journal of Language Education, 2026)
Recent research confirmed that idioms were one of the most complex aspects of learning English because their meanings were influenced by cultural differences, context, and limitations in the target language. Considering this fact, this study explored idiomatic expressions in the film Bilal: A New Breed of Hero to identify their types and meanings, while emphasizing the urgency of learning idioms in the context of English as a foreign language. This study employed a qualitative descriptive method with a discourse analysis approach, referencing Fernando's classification of idioms into three categories: pure, semi-literal, and literal. Data in the form of dialogues in the film containing idioms were analyzed through semantic and narrative context studies. The results of the study showed that the majority of idioms fell into the semi-literal categorization, combining literal and figurative meanings. In addition to functioning as stylistic elements, idioms also strengthened characterization, depicted conflicts, and represented Arab-Islamic cultural values. The film Bilal: A New Breed of Hero was considered a suitable subject for study because it presented the use of idioms in an authentic context while reflecting cultural values. Thus, this research was expected to contribute to the development of semantic studies, enrich language learning strategies, and enhance cross-cultural understanding.